EXPLORING EDUCATION FINANCING FOR STUDENTS IN THE MADRASAH IBTIDAIYAH TEACHER EDUCATION PROGRAM: A QUALITATIVE STUDY - Saugi, Wildan; Purwoko, Purwoko; Warman, Warman; Mulawarman, Widyatmike Gede (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2024)
This study aims to explore the financing of education for students of the Madrasah Ibtidaiyah Teacher Education Study Programme at UINSI Samarinda. Using a qualitative approach, this study collected data through in-depth interviews, which enabled the exploration of students' experiences and perspectives on sources of financing, challenges faced, and adaptation strategies applied. The results identified three main categories: Financing Sources, which show the important role of parental support and scholarships; Financial Challenges, which include rising tuition fees and limited access to scholarships; and Adaptation Strategies, which reflect students' efforts in managing finances and seeking additional opportunities. The findings highlight the complexity of the financial situation faced by students and the importance of better support from educational institutions. The implications of this research suggest the need for policies that create more equitable access to financial resources for students, as well as institutional support to help overcome the challenges involved in financing education. This research contributes to the understanding of the financial context of Islamic education, especially in higher education in Indonesia.